LIVING HADIS: GENEALOGI, TEORI, DAN APLIKASI - Saifuddin Zuhri Qudsy (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Within a decade, the study of Living Qur’an and Living Hadithand has flourished in Indonesia. Number of research about phenomena of either practices of rituals has been done. This article, departs from that fact, endeavors to explore model of living hadith, from its genealogical presence, theories that have been applied, up to technic which used into various kinds of research.